High‐Power, High‐Efficiency Tm:YAG and Ho:YAG Thin‐Disk Lasers. Issue 3 (31st January 2018) - Zhang, Jinwei; Schulze, Felix; Mak, Ka Fai; Pervak, Vladimir; Bauer, Dominik; Sutter, Dirk; Pronin, Oleg
Abstract: Continuous‐wave Tm:YAG and Ho:YAG thin‐disk lasers with maximum optical‐to‐optical efficiencies of 41% and 58% respectively are presented. Pumped by a 780 nm laser diode, the Tm:YAG laser generated a maximum output power of 24 W. In comparison, the Ho:YAG laser, pumped by a fiber laser at 1908 nm, delivered a maximum output power of 50 W. The reported output powers are, to the best of our knowledge, the highest among all thin‐disk lasers emitting at ≈2 μm, and provide a solid foundation for the further development of next‐generation 2 μm thin‐disk technologies. Abstract : Two different gain materials—Tm:YAG and Ho:YAG— are investigated in thin‐disk configuration. Using a 72‐pass pump cavity, thin‐disk lasers with high powers and optical‐to‐optical efficiencies at 2 μm have been realized, paving the way for further scaling of power towards kW‐level based on thin‐disk technology.